Shari'a governance in Bahrain: Analysing the Islamic banking industry's implementation of the newly issued regulatory Shari'a governance module - Abdulrahman Al-Saadi; M. Kabir Hassan; Ahmed Mansoor Alkhan (Journal of Risk and Financial Management, 2022)
Shari'a governance is considered a crucial element of the Islamic banking industry. As recent as 2017, Islamic banks in the Kingdom of Bahrain were required by the regulator to have only a Shari'a Supervisory Board and an internal Shari'a function. In 2017, the Central Bank of Bahrain issued a new Shari'a Governance module (SG) in its rulebook, requiring all Islamic banks to have at least two internal Shari'a departments instead of one, mandated external Shari'a auditing, and maintaining the necessity of having a Shari'a Supervisory Board. In this study, through an empirical enquiry, we analyse how the Islamic banking industry implemented this new module. The empirical results revealed that there seems to be an implementation gap between Islamic retail and wholesale banks, where the former have fully implemented the new Shari'a governance requirements, while the latter were given exemptions to postpone its implementation.
Keywords: G11; G14; G18; G21; G33; C00; 650; Shari’ a governance; Shari’ a audit; regulation; Islamic finance